DESIGN OF RESIDENTIAL ARRAYS USING GEOINFORMATION TECHNOLOGIES: Array - Korotkov, V.; Pomortseva, O. (Municipal economy of cities. Series: «Economy science», 2021)
The article examines the current problem of designing housing arrays. They would solve not only the problem of resettlement, but also all related problems, including parking of personal cars, employment of residents, a sufficient number of places for children in schools and kindergartens. In other words such housing arrays would be comfortable to live in and would have necessary infrastructure. Analysis of global design trends shows that these problems are solved in the design of satellite cities or semi-autonomous suburban areas. We have identified the existing pros and cons of these different approaches to design. We have chosen a centric planning approach semi-autonomous area as the most rational and efficient in urban planning. We used the ArcGIS geographic information system and a vector map to analyze the existing territory of Kharkiv and to select the construction site and further design the location of buildings and infrastructure. In particular, the “buffer zones” were used for the further placement of schools, kindergartens and shops. The usage of the "buffer zones" made it possible to locate these institutions optimally, depending on the number of potencial citizens. Basing on the historical aspects of Kharkiv, a quarterly division and quarterly buildings were chosen for the projecting area, due to the fact that each quarter will have its own urban ecosystem. An algorithm for performing such works was developed by designing a residential area. It can be divided into certain stages. This algorithm can be applied while performing similar works not only to Kharkiv, but also to other cities of Ukraine and the world. The article demonstrated the possibilities of geographic information systems in the design of new types of residential areas with highly developed social and transport infrastructure, harmonious development, as well as attractive to stakeholders and future residents.